Strategi Pengembangan Kompetensi Aparatur Sipil Negara oleh Badan Pengembangan Sumber Daya Manusia Provinsi Kepulauan Riau - Ummidiah Islamiaty; Ella Afnira (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2022)
Competency development is an important process in employee retention and performance to prepare professional Apparatus Resources (SDA). The agency responsible for the implementation of human resource development for state, district and city governments in accordance with statutory regulations. The location of this research was carried out in one of the local government organizations, namely the Riau Islands Human Resources Development Agency (BPSDM). The study used qualitative methods, collecting data through interviews with resource persons. This study uses data analysis techniques and SWOT analysis. This internal factor analysis was compiled from the strengths and weaknesses of the Riau Islands BPSDM, and external factors taken from the opportunities and threats of the Riau Islands BPSDM in developing ASN competencies.